A Taxonomic Revision of the Genus Poeppigia (Fabaceae: Dialioideae) - Falcão, Marcus José De Azevedo; Mansano, Vidal De Freitas (Phytotaxa, 2021)
Poeppigia is a Neotropical genus of legumes that occurs from Mexico and Cuba to eastern Brazil and is considered until now to be monospecific with two varieties. Being one of the 17 genera in the subfamily Dialioideae, Poeppigia stands out as one of the few genera with not reduced perianth and androecium, representing a possible link between this subfamily and the other Fabaceae. The genus was never revised since several taxa were described in the XIX century and lack of recent studies and proper typification. Here we revised the genus taxonomically with the analysis of more than 400 specimens and proposed the acceptance of two species: P. procera, distributed on tropical forests from Mexico to Amazon and Southeast Brazil and P. densiflora, endemic of Brazilian Caatinga. The two species are distinct for many characters as habitus, size of branch, leaf and fruits, number of leaflets, stipules and bracts and form of inflorescence. Seed, embryo, pollen and seedling descriptions, conservation assessments, illustrations, maps of distribution and an identification key are presented. Nomenclatural, biogeographical, and ecological comments and three new lectotypifications are made.